PENYULUHAN TATA KELOLA DANA KAS KECIL MENGGUNAKAN METODE SALDO DANA TETAP BAGI UMKM DI YAYASAN KIBAR FOUNDATION - Dicky Arisudhana; Mia Laksmiwati; Sugeng Priyanto; Taqwa Putra Budi Purnomo Sidi Hiram (CV. Denasya Smart Publisher, 2024)
This community service activity was carried out at the Kibar Foundation. Participants in this activity were Micro, Small and Medium Enterprises (MSMEs) who live in the Special Capital Region of Jakarta. The city of Jakarta as the capital of the Republic of Indonesia has community potential and resources that support entrepreneurial activities. This condition is proven by the increasing number of members of MSME business actors at the Kibar Foundation every year. In line with the increase in the number of MSME business actors, there are several problems faced by them, namely the low level of knowledge and understanding in managing, recording, reporting and accounting for petty cash funds, especially using the imprest fund method. The aim of this community service activity is to provide knowledge and understanding through counseling and outreach related to the problems faced by MSME business actors at the Kibar Foundation, namely managing petty cash funds to finance relatively small expenditures with a frequency of occurrence. transactions are high. The method used in community service activities is the lecture method which is then followed by discussion, questions and answers and case simulations. Evaluations carried out before the end of the activity showed that the majority of participants understood and really understood the counseling or socialization material presented. The evaluation results also illustrate that all participants who attended the activity felt they had benefited and were satisfied with the implementation of this activity.